Archaeological Research Of The Uzbek-Italian Archaeological Expedition During The Years Of Independence - Farmanova Gulnara Komilevna (Genius Journals, 2023)
The author of the article argues that after the declaration of independence of Uzbekistan, the opportunity for scientific research, including archaeological research, was opened in our country for scientists from different countries who perceive the history of our Motherland as an integral part of the history of all mankind. As a result of joint archaeological expeditions and research at the present stage, certain factual material has been accumulated in Samarkand Sogd. This largely indicates the importance of the history and culture of Samarkand and its environs in the study of the historical and cultural heritage of the entire Central Asian region. Important achievements in the field of historical and archaeological study of Samarkand Sogd during the period under review are also the works of Uzbek and Italian archaeologists, who made a huge contribution to the development of the Uzbek school of archeology, applied new methods of archaeological research using the latest technologies and technical means, which made it possible to make new discoveries on the region being studied.
Keywords: Uzbek-Italian archaeological expedition; Samarkand Sogd; ancient